Research on Resistor-Loaded Half-Ellipse Antenna System for GPR Application - Xueping Li; Jinjin Shao; Yu Zhang (International Journal of Antennas and Propagation)
A resistor-loaded half-ellipse antenna system mounted on a vehicle as a candidate for the exploration of the lunar subsurface is investigated. The antenna system includes two identical half-ellipse antennas, one is used for transmission, and the other is for reception. A resistive loading technique for broadening the bandwidth and improving impulse radiation is introduced. The performance of the proposed antenna with different height above ground surface is studied, and the influence of the vehicle on the antenna is analyzed. Then the antenna is manufactured and mounted on a vehicle as some tests are done. The simulated and measured antenna VSWR and radiation patterns are compared together, and good agreements between them are achieved.